Short Term Outcomes after Elective Gastrointestinal Surgery in Octogenarians: A Retrospective Matched Cohort Study - Kandel, Bishnu Prasad; Koirala, Nishnata; Sharma, Deepak; Maharjan, Narendra; Pradhan Maskey, Sumita; Bhandari, Ramesh Singh; Joshi Lakhey, Paleswan (Journal of Institute of Medicine Nepal, 2025)
Introduction The incidence of gastrointestinal surgical conditions like malignancy increases with age. There is growing requirement of gastrointestinal surgery in elderly patients due to the aging of general population. Gastrointestinal surgery in octogenarian patients posses an unique challenges due to decreased functional status of organs and higher incidence of co-morbidities. Methods In this retrospective study we compared the co-morbidities and perioperative outcomes of octogenarian patients with case matched younger patients. There were 2115 patients who underwent gastrointestinal surgery from October 2021 to September 2024 out of which thirty four were octogenarian patients. Sixty eight younger patients who underwent similar surgical procedures were selected for comparison. Patients’ data were obtained from the medical records and the outcomes of surgery in two groups were compared. Results Octogenarian patients had more co-morbidities compared with younger patients. Occurrence of major postoperative complications (23.5% vs 8.8%; p value 0.04) and cardiac complications (20.6% vs 4.4%; p value 0.01) were higher in octogenarians. Postoperative hospital stay, intensive care unit stay, occurrence of overall complication and mean comprehensive complication index was similar in two groups. Conclusion Octogenarian had higher occurence of major complications after gastrointestinal surgery. Proper perioperative care is required for surgical management of octogenarian patients.